Smartland Korea : mobile communication, culture, and society - Jin, Dal Yong, 1964- (Book collections on Project MUSE., 2017)
"This book examines mobile communication, culture, and society in the context of Korean smartphones, analyzing the role of smartphones and apps as major components of Korea's national economy and culture, the sociocultural factors involved in the growth of mobile games and youth culture, and the context of globalization. It discusses the evolution of the smartphone, its recent growth in Korea, Korea's reception of the iPhone in 2009 and the recent growth of Samsung's Galaxy in the global market, key aspects of smartphones and app services in Korea and their implications for the app economy, the digital divide in terms of smartphones, mobile gaming, and young Koreans' engagement with a local app platform, Kakao Talk."--Provided by publisher.